Molecular rotational diusion detected by dierential fluorescence energy - Torga, Jorge Román; Marconi, Mario; Negri, Martin; Aramendia, Pedro (My University, 2000)
In this paper, we present a complete study of the influence of the molecular rotational diffusion movement in the fluorescence signal when a sample is excited by two short pulses. The study includes the calculations of this effect for ellipsoidal molecules. Experimental results are presented that show a fluorescence behavior influenced by the molecular rotational diffusion movement with temporal characteristics that agree with our calculations.
Keywords: UTN; Facultad Regional Delta; Molecular rotational; Fluorescence signal; Ellipsoidal molecules; Fluorescence energy